Retroperitoneal extrarenal angiomyolipoma: how to differentiate it from retroperitoneal liposarcoma with a case report - Jafari, Anya; Sanei Taheri, Morteza; Taghizadeh-Hesary, Farzad (European Journal of Oncology and Environmental Health, 2019)
Extrarenal retroperitoneal angiomyolipomas (ERAMLs) are extremely rare benign lesions that can imitate some other benign and malignant retroperitoneal masses. In order to prevent the imposing an unnecessary debilitating treatment for these patients, recognizing its clinical characteristics (including imaging features) matters a lot. We present a very rare case with ERAML to shed light, especially on its radiological attributes. We proposed a pair of radiologic findings that may have the potential to differentiate ERAML from its malignant differential diagnosis (i.e. retroperitoneal liposarcoma) that are intratumoral aneurysmal vessels and intratumoral hemorrhage. We presented this especial case report in hope to guide further studies to make a valuable clinical blueprint to differentiate ERAML from retroperitoneal liposarcoma.